Analysis of The Influence of Trust and Commitment on Organizational Performance Through Mediation of The Quality of Partnership Relationships (Study on TVRI Central Java) - Handayani, Bahtera Afrikani Sri Wuri; Perdhana, Mirwan Surya (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
TVRI Central Java, a public broadcasting institution in Indonesia, faced declining partnerships (2018–2022) and unmet PNBP revenue targets, underscoring the need to analyze how trust and commitment enhance organizational performance through partnership quality. This study examines the influence of trust and relationship commitment on partnership quality and their combined impact on organizational performance. Data from 119 TVRI partners were analyzed using SEM-AMOS to test five hypotheses in a structured model. Trust and commitment significantly improve partnership quality (H1, H3) and directly enhance organizational performance (H2, H4), with partnership quality itself driving performance (H5). Relationship commitment emerged as the most dominant factor. The study validates prior theories (Kac et al., 2016; Mukhsin, 2017) while offering practical strategies for public media institutions, such as reinforcing transparency and incentives, to revive partnerships and achieve fiscal targets. Future research could explore sector-specific barriers or digital tools to strengthen these dynamics.